Kejadian Disfungsi Ereksi pada Pria yang Menyandang Diabetes Melitus di Puskesmas Wilayah Jakarta Barat - I Gusti Made Sashy Byomantara; Fadil Hidayat (Syntax Idea)
Erectile dysfunction is the inability to achieve or maintain an erection of the penis. Erectile dysfunction can occur in a third of men and more than half of men with Diabetes Mellitus. The prevalence of erectile dysfunction in men with Diabetes Mellitus is still high. This study aims to obtain data on the incidence of erectile dysfunction at the West Jakarta District Health Center. This research is descriptive with cross- sectional design. The research subjects were 90 respondents. Data collection using the questionnaire The International Index of Erectile Function Questionnaire (IIEF)-5. The results showed that the number of respondents who did not experience erectile dysfunction was 16 people (17.8%) while the respondents who experienced erectile dysfunction were 74 people (82.2%) with 22 people (29,7%) experiencing mild dysfunction, 12 people (16,2%) had mild - moderate dysfunction, 27 people (36,5%) had mild dysfunction, and 13 people (17,6%) had severe dysfunction. The conclusion of the study was that the incidence of erectile dysfunction at the West Jakarta Health Center was 22 respondents with mild erectile dysfunction (29,7%), 12 respondents with mild - moderate erectile dysfunction (16,2%), 27 respondents with mild erectile dysfunction (36,5%), and 13 respondents with severe erectile dysfunction (17,6%).